Vertical urban factory - Rappaport, Nina (New York : Actar Publishers, 2018)
This book focuses on the spaces of production in cities that are significant in their design and contribute to a vital urban environment. This book reexamines the modernist and contemporary factory, along with labor issues in the city and the impact of globalization through the lens of an urbanist, while provoking future scenarios for urban manufacturing. It shows now factories are cleaner and greener, smaller and taller, hybrid and flexible, they can be reintegrated in city life, creating a new paradigm for a sustainable, mixed-use, and more self-sufficient industrial urbanism.
Includes bibliographical references and index.
Keywords: Factories -- Design and construction; Factories -- Social aspects; Architecture, Industrial; Sociology, Urban; Architecture, Industrial